From Financial Crisis to Great Recession: The Role of Globalized Banks - Aiyar, Shekhar (American Economic Review, 2012)
This paper provides evidence of the role of globalized banks in transmitting financial stresses to the real economy during the global financial crisis. A novel dataset is constructed from quarterly balance sheet reports provided by all UK-resident banks to the Bank of England. I find that the shock to bank funding from non-resident creditors was transmitted domestically through a significant reduction in bank credit supply. Resident subsidiaries and branches of foreign-owned banks reduced lending by a larger amount than domestically-owned banks, while the latter calibrated the reduction in domestic lending more closely to the size of the funding shock.